Optimization of the reverse electrodialysis power output through the ratio of the feed solutions salinity - Zoungrana, Ali; Cakmakci, Mehmet (INST ENGINEERING TECHNOLOGY-IET, 2021)
A lab-scale reverse electrodialysis module was constructed to highlight the optimal feed solutions concentration, the flow rate and their importance in improving the power density in reverse electrodialysis. The results showed that the increase of the feed solutions flow rate is beneficial by augmenting the power output, but too high flow rate harms the process performance. Even though the highest power density (0.54 W/m(2)) was obtained at 60 mL/min with 4 and 428 mm feed solutions, the optimal flow rate determined by this study was 30-45 mL/min. It has been discovered that the variation of NaCl concentration in the low compartment was more sensible in affecting the reverse electrodialysis performance compared to the high compartment solution. The NaCl concentration of 6 and 684 mm appeared to be the optimal values for low compartment and high compartment solutions, respectively, for high performance and efficient power generation with reverse electrodialysis using seawater and river. When 1/3 of the minimum flow rate of the Ceyhan River running into the Mediterranean Sea is operated in the reverse electrodialysis system, at least 17.18 x 10(6) KWh electrical energy was estimated to be generated per year, with a power density of 0.705 m(2)/W.
Keywords: EXCHANGE MEMBRANE; ENERGY; WATER; PERFORMANCE; GENERATION; TECHNOLOGY; BRINES; SYSTEM; Science & Technology - Other Topics; Energy & Fuels; Engineering